ATLAS OF COLORS Colors for better therapeutic environments - LAW-BO-KANG, EMMA (My University, 2023)
Perception may be defined as the process by which individuals receive, recognize, organize and interpret sensory information in order to give meaning to their environment. In the psychiatric field, it turns out several mental illnesses alter the senses of perception for patients. Architecture plays a critical role in psychiatric care, as the physical environment can have a significant impact on the emotional and psychological well-being of individuals receiving treatment. The ability of color to impact human emotions, behavior, and well-being is significant and makes it a powerful tool that can be used to achieve desired outcomes. This color impact on human well-being is particularly important in healthcare settings, where it has been shown to influence people’s mood, perception of pain, and recovery time. Therefore, it is important for architects to consider the impact of color in their designs and to use color in a thoughtful and intentional way to enhance patients’ well-being and recovery. The thesis rests on the analysis of the use of color in space and its effect on people diagnosed with Post-Traumatic Stress Disorder (PTSD), in the context of built environments. It then delves into different ways in which color can be used to support trauma recovery and promote feelings of safety and comfort. This includes an examination of color psychology, color symbolism, and the ways in which different hues and other color characteristics can impact emotional states. The identification of stress-suitable colors led to the elaboration of a color palette. By suggesting this tool, the thesis aims to provide practical guidance and inspiration to architects for designing more supportive and healing environments in the psychiatric field. This thesis aims to bridge the gap between the psychiatric and architectural fields, shedding light on the importance of designing for individualswith disorders. It offers a valuable resource for professionals dedicated to creating environments that promote healing and well-being for those who have experienced trauma. More, it approaches a field with a lack of research and sets an explorative base for further research on the topic.
Keywords: color perception, mental health, therapeutic environment, psychiatric architecture, trauma-informed design